In vitro and in vivo growth inhibitory activities of cryptolepine hydrate against several Babesia species and Theileria equi - Batiha, Gaber El-Saber; Beshbishy, Amany Magdy; Alkazmi, Luay M.; Nadwa, Eman H.; Rashwan, Eman K.; Yokoyama, Naoaki; Igarashi, Ikuo (PLOS Neglected Tropical Diseases, 2020)
Author summary The development and evaluation of new treatment strategies against Babesia and Theileria parasites have become increasingly urgent due to the emergence of parasite resistance and unwanted toxicity side effects by current chemotherapies. On the other hand, vaccination is a cheaper, reliable and sustainable option. Unfortunately, it has not worked well for the protozoan diseases because they possess ingenious mechanisms to evade the host immune system, rendering treatment the most suitable approach for their control. Sadly, only diminazene aceturate (DA) and imidocarb dipropionate have passed clinical trials for the treatment of piroplasmosis. However, these drugs cause many adverse effects and not approved yet for human medicine. Cryptolepine (CRY) is a pharmacologically active indoloquinoline alkaloid isolated from the roots of the shrub Cryptolepis sanguinolenta. CRY is reported to possess various pharmacological activities, including antifungal, anti-mycobacterial, and potent antiplasmodial activities. In the present study we evaluated the effects of CRY against the growth of Babesia bovis, B. bigemina, B. divergens, B. caballi and Theileria equi in vitro and its chemotherapeutic potential on Babesia microti in mice. Furthermore, we investigated the effect of combination between CRY with the current babesiocidal drugs such as DA, atovaquone (AQ) and clofazimine (CF) in vitro and in vivo.